2016
DOI: 10.5603/gp.2016.0001
|View full text |Cite
|
Sign up to set email alerts
|

Advanced oxidation protein products and malondialdehyde — the new biological markers of oxidative stress — are elevated in postmenopausal women

Abstract: Objectives: The aim of the study was to measure advanced oxidation protein products (AOPPs) as markers for oxidative stress to evaluate cardiovascular risk in pre-and postmenopausal women and to compare the results with malondialdehyde (MDA) levels. Material and methods:Twenty premenopausal women and 84 naturally postmenopausal patients were enrolled in the study. AOPP and MDA plasma levels were measured. The postmenopausal group was further subdivided into two groups: postmenopausal age of 40-49 and of 50-59 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 37 publications
2
8
0
1
Order By: Relevance
“…The most commonly used method to monitor oxidative stress is the measurement of parameters of antioxidant abilities and oxidative damage in the serum, since it is the least invasive and easily available method. It was found that the serum concentrations of oxidative damage markers (e.g., TBARS, AOPP, PCG) were higher, and the serum indices of antioxidant abilities parameters (e.g., GSH) were lower in postmenopausal women than in premenopausal women [33,34,35]. In addition, the glucose and lipid metabolism disorders are observed in postmenopausal women [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used method to monitor oxidative stress is the measurement of parameters of antioxidant abilities and oxidative damage in the serum, since it is the least invasive and easily available method. It was found that the serum concentrations of oxidative damage markers (e.g., TBARS, AOPP, PCG) were higher, and the serum indices of antioxidant abilities parameters (e.g., GSH) were lower in postmenopausal women than in premenopausal women [33,34,35]. In addition, the glucose and lipid metabolism disorders are observed in postmenopausal women [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…(2004) on exposure of blood albumin to oxidative and carbonyl stresses products AOPPs become generated. AOPPs have a pro-inflammatory character, and act as inflammatory mediators that stimulate the recruitment of more neutrophils and monocytes and activate the T-lymphocytes oxidative ignition and dendritic cells (Cakir et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that although ox-LDL and MDA were higher in post-menopausal women without T2DM, this difference was disappeared in patients with T2DM, either pre-or post-menopausal ( gure1). Yichuan Wen et al reported that ox-LDL mainly increased following menopause in non-diabetic women due to loss of anti-oxidative properties of estrogen after menopause [25] similar to MDA [26]. The interaction analysis showed that T2DM and menopausal status had no signi cant joint effects on ox-LDL and MDA levels.…”
Section: Discussionmentioning
confidence: 98%